Mathematical Connections and Their Relationship to Strategic Intelligence Among Students of Mathematics Department in The Colleges of Education - MUHAMMAD, M. M. SHAIMA HUSSEIN; FARIS, DR. ILHAM JABBAR (The journal of contemporary issues in business and government, 2021)
The present research aims to study the relationship between mathematical Connections and strategic intelligence for students of the mathematics department in the College of Education by answering the following questions: Do students of the Department of Mathematics in the College of Education possess mathematical Connection skills? Do students of the mathematics department in the College of Education possess strategic intelligence? What is the direction and strength of the Connectional relationship between mathematical Connections and strategic intelligence among students of the Mathematics Department in the College of Education? In order to achieve the goal of the research and answer its questions, the researcher developed a set of hypotheses and the research community was identified, which represents students of the mathematics departments in the Faculties of Education in Baghdad Governorate (College of Education for Pure Sciences - Ibn Al-Haytham / Baghdad University and the College of Education Al-Mustansiriya University). The fourth is from the mathematics department at the College of Education, Ibn al-Haytham, as it consisted of (130) male and female students, divided into (79) male and (51) female students.